The Role of Notary Supervision Institutions and Notary Responsibilities for Violations of Their Obligations - Silvia Loka; Ariawan Gunadi (Jurnal Indonesia Sosial Teknologi, 2024)
The objective of this study is to further examine regulations related to the Notary Supervisory Board concerning the supervision of notarial ethical codes and to assess the responsibilities of notaries in case of duty violations. The research method employed is normative, utilizing a legislative approach and descriptive analysis. The findings of the study aim to evaluate the effectiveness of the Notary Supervisory Board in fulfilling their duties in terms of legislation, assess the need for regulatory updates to enhance supervisory effectiveness, and evaluate the impact of notarial duty violations on parties involved in transactions or acts prepared by notaries.